(untitled) (COLOMBIAN JOURNAL OF ADVANCED TECHNOLOGIES, 2024)
This document presents the development process and initial testing phases of an electronic system designed to facilitate web-based communication for an industrial device. The industrial device operates using Modbus RTU communication, and the system utilizes the MQTT telemetry protocol, which is integrated into a 32-bit microcontroller. The microcontroller operates within a real-time operating system framework, ensuring efficient communication management. The system integration with a PLC has been established during the equipment development, and validation has been achieved through the utilization of a comprehensive database, Python scripts, and the incorporation of visualization capabilities provided by a web-based platform. The prototype is capable of remotely reading and modifying Modbus registers through a web interface, which not only allows parameter adjustments but also provides access to historical measurement records, enhancing the overall functionality of the industrial device.